Peran Organisasi Pramuka Dalam Menumbuhkan Jiwa kepemimpinan Pada Mahasiswa di Universitas Islam Negeri Fatmawati Sukarno Bengkulu - Izalia, Berti; Suhirman; Syahbudin, Rizkan (JPT : Jurnal Pendidikan Tematik, 2022)
The formulation of the problem in this study are: 1. How is the role of the Scout organization in fostering leadership in students at Fatmawati Sukarno State Islamic University Bengkulu? 2. What are the supporting and inhibiting factors of the scouting organization in growing the spirit of leadership at Fatmawati Sukarno Bengkulu State Islamic University? The aims of this study were (1) to identify and understand the role of the Scout organization in fostering leadership spirit in students at Fatmawati Sukarno Bengkulu State Islamic University, (2) to determine the supporting and inhibiting factors of students in joining the Scout organization in fostering leadership spirit in students at Fatmawati Sukarno State Islamic University Bengkulu. To answer the above objectives, this study uses qualitative techniques, namely the process of systematically searching and compiling data obtained from interviews, field notes and other materials. The results of data analysis found (1) the implementation of scouting activities at Fatmawati state Islamic university carried out as in Generally, there are ceremonial sessions, seasons/materials, and practices and outbounds. (2) Scouting activities at Fatmawati state Islamic university have contributed a lot in fostering the self-reliance of students, responsibility and leadership spirit of the education center will be honed with scouting activities by making them pinru/wapinru in small things because it is very effective.